Effect of surgical shoes on brake response time after first metatarsal osteotomy—a prospective cohort study. Issue 1 (December 2016) - Dammerer, Dietmar; Braito, Matthias; Biedermann, Rainer; Ban, Michael; Giesinger, Johannes; Haid, Christian; Liebensteiner, Michael; Kaufmann, Gerhard
Abstract Background The aim of this study is to assess patients' driving ability when wearing surgical shoes following right-sided first metatarsal osteotomy. Methods From August 2013 to August 2015, 42 consecutive patients (mean age 54.5 years) with right-sided hallux valgus deformity underwent first metatarsal osteotomy. Patients were tested for brake response time (BRT) 1 day preoperatively (control run) and at 2 and 6 weeks postoperatively. Two different types of foot orthosis were investigated. BRT was assessed using a custom-made driving simulator. Results Preoperative BRT was 712 msec (standard deviation (SD), 221 msec). BRT was significantly slower at all tested postoperative times than preoperatively (p < 0.001). The patients showed significant impaired brake response time when wearing surgical shoes. Mean global American Orthopaedic Foot and Ankle Society (AOFAS) outcome score and AOFAS pain and alignment subscores increased postoperatively (p < 0.001). Conclusions From our findings, we recommend driving abstinence for a minimum of 6 weeks postoperatively when using a surgical shoe after bunionectomy. However, patients should have sufficient recovery, exercise, and training before resuming driving a car, because safety is always a priority. Trial registration ClinicalTrials.gov, NCT02354066